Genetic Predisposition to Persistent Human Papillomavirus-Infection and Virus-Induced Cancers - Helen V. Espinoza; Kim T. Ha; T. Pham; J. Luis Espinoza (2021)
Human papillomaviruses (HPVs) are the most common sexually transmitted pathogens worldwide and among the more than 200 identified HPV types, approximately 15 high risk (HR-HPV) types are oncogenic, being strongly associated with the development of cervical cancer, anogenital cancers and an increasing fraction of head and neck squamous cell carcinomas (HNSCC). HPV-associated cervix cancer accounts for 83% of HPV-attributable cancers, and more than two-thirds of those cases occur in developing countries. Despite the high frequency of HPV infections, in most cases, the virus is cleared by the host immune response and only a small proportion of infected individuals develop persistent infections that can result in malignant transformation, indicating that other elements, including biological, genetic and environmental factors may influence the individual susceptibility to HPV-associated cancers. Previous studies have quantified that heritability, in the form of genetic variants, common in the general population, is implicated in nearly 30% of cervical cancers and a large number of studies conducted across various populations have identified genetic variants that appear to be associated with genes that predispose or protect the host to HPV infections thereby affecting individual susceptibility to HPV-associated cancers. In this article, we provide an overview of gene association studies on HPV-associated cancers with emphasis on genome-wide association study (GWAS) that have identified novel genetic factors linked to HPV infection or HPV-associated cancers.